Design of an endoscopic OCT probe based on piezoelectric tube with quartered outside electrodes - Hu, Jinyuan; Wu, Sujian; Shi, Guohua; Fan, Jinyu; Yu, Haoyang; Chen, Sixu (Frontiers in Bioengineering and Biotechnology, 2024)
In this study, a micro intraocular OCT probe was fabricated using a piezoelectric tube with quartered outside electrodes as a driver, which could realize Lissajous scanning of the movement track at the end of a single mode fiber and enter the eyeball through the scleral opening to perform real-time tomography of the fundus retina. Due to the particularity of the structural design, the outer diameter of the endoscopic OCT probe in this study can be replaced by 13G (outer diameter 2.41 mm)-25G (outer diameter 0.51 mm), to achieve different imaging field sizes and ensure safe access to the ocular scleral incision. In this paper, the principle, theoretical derivation, and feasibility analysis of the application of a piezoelectric tube with quartered outside electrodes on the snooping probe in OCT are introduced, as well as the design characteristics, practical application and imaging situation of the endoscopic OCT probe are introduced, and the future direction of further research has prospected.